USING YOUNG ADULT LITERATURES READING MATERIAL IN INCREASING VOCABULARY ACHIEVEMENT FOR MIDDLE SCHOOL STUDENTS - Yanti Anggraini (JAMBI-ENGLISH LANGUAGE TEACHING, 2018)
Vocabulary is an important thing for language learning strategies (LLS) especially in learning English as a foreign language (EFL). Many foreign language learners are in desperate for learning the vocabulary. Learners are usually aware of the importance of words in a language and they also usually realize the fact that learning strategies can help them in their vocabulary learning. The aims of this study were to find whether or not (1) there was any significant difference in vocabulary achievement between before and after the students were taught by using young adult literature, (2) there was any significant difference in vocabulary achievement between the students who were in the experimental group and those of the control group, and (3) there were any significant differences in aspects of vocabulary between before and after the students were taught by using young adult literature. The result of paired samples t-test analysis showed that there was significant difference in vocabulary achievement between pre-test and post-test of the students who were taught by using young adult literature. The result of independent samples t-test analysis showed that there was significant difference in vocabulary achievement between the students who were in the experimental group and those of the control group. It means that Young Adult Literature as the reading material successfully increased the students’ vocabulary achievement in the experimental group.